What is wrong? perception of community health agents and endemies on the combat to aegypti aedes - França, Lays Santos (2019)
This study aimed to discuss the perceptions of Community Health Agents and Endemic Control Agents on the process of guiding the population regarding the prevention and control of Aedes Aegypti. This is a descriptive and exploratory study of qualitative nature, conducted with 07 Endemic Disease Agents and 12 Community Health Agents in a city in the interior of Bahia, whose data were collected through semi-structured interviews, recorded with the aid of tape recorder and analyzed through the technique of collective subject discourse, which allowed the construction of collective discourses. The results show that in the perception of such professionals, the population does not contribute to the prevention and control of Aedes Aegypti effectively, leaving only the professionals in question to act actively, and this work should be together with the population and the agents. We conclude that based on the results obtained the population is oriented towards care for the prevention of AA, however, most people do not put into practice what is passed on to them, so there is a need to implement activities to raise awareness of them.